3,4-Dihydroisoquinolinium Chlorochromate: A Mild and Effective Reagent for the Oxidation of Alcohols to Carbonyl Compounds and Arenes to Quinones - YURDAKUL, AYSE; OZEN, RECEP (Asian Journal of Chemistry, 2010)
A new chromium(VI) reagent, 3,4-dihydroisoqinolinium chlorochromate (DIQCC) was prepared and characterized. This reagent is suitable to oxidize various primary and secondary alcohols to the corresponding carbonyl compounds and antracene to anraquinone in a good yields.